2020
DOI: 10.3389/fmicb.2020.01594
|View full text |Cite
|
Sign up to set email alerts
|

Burkholderia cepacia Complex Taxon K: Where to Split?

Abstract: The objective of the present study was to provide an updated classification for Burkholderia cepacia complex (Bcc) taxon K isolates. A representative set of 39 taxon K isolates were analyzed through multilocus sequence typing (MLST) and phylogenomic analyses. MLST analysis revealed the presence of at least six clusters of sequence types (STs) within taxon K, two of which contain the type strains of Burkholderia contaminans (ST-102) and Burkholderia lata (ST-101), and four corresponding to the previously define… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
47
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(50 citation statements)
references
References 71 publications
3
47
0
Order By: Relevance
“…Overall, core-gene phylogenetic analysis was concordant with both ANIm and ANIb, and the designation of 6 taxon K isolates and 13 taxon K isolates [26] as B. aenigmatica. This dataset also revealed a unique intraspecies sub-clading, for which a limited amount of evidence was observed in previous datasets [27].…”
Section: Comparison Of Mlst and Core-gene Phylogenomics Clarifies Past Misidentification Of Taxon K Isolates And Identifies B Aenigmaticasupporting
confidence: 58%
See 4 more Smart Citations
“…Overall, core-gene phylogenetic analysis was concordant with both ANIm and ANIb, and the designation of 6 taxon K isolates and 13 taxon K isolates [26] as B. aenigmatica. This dataset also revealed a unique intraspecies sub-clading, for which a limited amount of evidence was observed in previous datasets [27].…”
Section: Comparison Of Mlst and Core-gene Phylogenomics Clarifies Past Misidentification Of Taxon K Isolates And Identifies B Aenigmaticasupporting
confidence: 58%
“…2a). This MLST analysis also placed the 13 industrial isolates previously identified as B. lata [26], the B. aenigmatica [27] type strain, and the additional B. lata Fig. 3.…”
Section: Comparison Of Mlst and Core-gene Phylogenomics Clarifies Past Misidentification Of Taxon K Isolates And Identifies B Aenigmaticamentioning
confidence: 64%
See 3 more Smart Citations